Pemanfaatan Tanah Lempung Untuk Menurunkan Konsentrasi Logam Pb Dan Cr Dari Limbah Cair Industri Percetakan Koran - Regina Giantika; Shinta Elystia; Zultiniar Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Characteristic of newspaper printing industry waste water has never been tested before, because there is still no waste water monitoring in an integerated way. This research utilizing clay to reduce heavy metal content of Cr contained in the waste water of newspaper printing industry. Preliminary analysis for Cr in waste water showed concentrations of these parameters exceed waste water quality standards of PERMENLH/5/2014. This study uses an ion exchange column with 5 cm diameter and 80 cm of height. The medium used is liquid waste newspaper printing and activated clay with a solution of H2SO4 2 M. The variation used is the calcination temperature is 200, 300, 400, and 500◦C and flow rate used is 2,7; 4; dan 5,3 ml/dt. The initial concentration Cr6+ ion is 0.838 mg/L. After processing the decline occurred in the ion concentration Cr6+ in every variation that is 0.334 to 0.582 mg/L. These results indicate that ion exchange method using activated clays are capable of removing concentration Cr6+ ion on wastewater printing. Overall, the variety used in this study to give effect to decreased levels of chromium and Lead in wastewater printing, also evidenced in Cr6+ ion removal efficiency ranged between 60.2% - 30.6%. KTK value of the clay is greater than the value of KA clay. Proving that the clays have a greater ability as compared to the ion exchange resin as an adsorbent. Keywords: printing waste water, ion exchange, activated clay, temperature calcination and flow rate, KTK and KA.